(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Due to global migration, multilingual classrooms are currently a common feature not just in postcolonial contexts but also in developed economies. The perceived challenges created by multiple languages in single classrooms have been well documented, and all stakeholders have to be involved in finding strategies to overcome these challenges and change perceptions. Using a case study design and sociocultural theory as lens, this study explored the perspectives and experiences of teachers with teaching and learning in resource-constrained multilingual classrooms. The participants were teachers (N=67; female n=51; male n=16) from nine schools in Gauteng Province of South Africa. The findings suggest that the participants were divided in their perceptions and experiences of multilingual classrooms. While some viewed multilingualism as a constraint to effective teaching and learning; others wanted more to be done to accommodate learners. It is evident that teachers prioritise the necessity for pre-service teacher education that focus on teaching pedagogy appropriate for the multilingual context they work in every day. In addition, the teachers emphasised a range of support strategies they currently use. It is argued that structured variations of the teachers' strategies be developed and distance education employed for the professional development of in-service teachers working in multilingual contexts.